Exploring the implementation of lesson study combined with contextual learning to improve mathematics understanding among pre-service elementary teachers - Yani T, Ahmad; Winarji, Agus; Meldi, Nadya Febriana; Novianti, Metia; Mirza, Ade (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study seeks to explain how the integration of Lesson Study and Contextual Teaching and Learning supports pre-service elementary teachers in developing deeper conceptual understanding of mathematics and cultivating reflective teaching habits. The focus lies in examining how the combined approach encourages meaningful engagement with geometric and measurement concepts through real-life contexts. Method: A descriptive qualitative design was applied by following the Lesson Study cycle of collaborative planning, classroom implementation, and reflective discussion. Data were gathered through observations, semi-structured interviews, field notes, and assessments conducted during the Geometry and Measurement course. The analysis used the Miles and Huberman framework to identify, organize, and interpret emerging patterns in students’ learning behavior. Findings: The integration of Lesson Study and contextual strategies led to more active participation, stronger collaboration, and clearer conceptual reasoning among pre-service teachers. Contextual problems helped students connect abstract geometric ideas with real situations, while the reflective phase allowed misconceptions to become learning opportunities. Both lecturers and students demonstrated noticeable professional growth as they engaged in continuous cycles of inquiry and refinement. Significance: The study highlights that combining structured reflection with contextual learning can enhance mathematical engagement and strengthen conceptual understanding among future teachers. This integrated model offers a promising pathway for preparing reflective, skillful, and context-aware mathematics educators at the higher-education level.